2012
DOI: 10.1021/jp3023887
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Rate Rules for Alkyl + O2 Reactions. 2. The Isomerization, Cyclic Ether Formation, and β-Scission Reactions of Hydroperoxy Alkyl Radicals

Abstract: The unimolecular reactions of hydroperoxy alkyl radicals (QOOH) play a central role in the low-temperature oxidation of hydrocarbons as they compete with the addition of a second O(2) molecule, which is known to provide chain-branching. In this work we present high-pressure rate estimation rules for the most important unimolecular reactions of the β-, γ-, and δ-QOOH radicals: isomerization to RO(2), cyclic ether formation, and selected β-scission reactions. These rate rules are derived from high-pressure rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
203
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(218 citation statements)
references
References 57 publications
14
203
1
Order By: Relevance
“…Villano et al 14 calculated the high-pressure-limit rate coefficients of these reactions, in the reverse, exothermic direction, for C 2 -C 5 and selected C 6 and C 7 olefins at the same level of theory used in their previous work 11,13 .…”
Section: Update 6: Qooh = Olefin + Ho 2 (Radical Site β To Ooh Group)mentioning
confidence: 99%
See 1 more Smart Citation
“…Villano et al 14 calculated the high-pressure-limit rate coefficients of these reactions, in the reverse, exothermic direction, for C 2 -C 5 and selected C 6 and C 7 olefins at the same level of theory used in their previous work 11,13 .…”
Section: Update 6: Qooh = Olefin + Ho 2 (Radical Site β To Ooh Group)mentioning
confidence: 99%
“…Bugler et al 5 revisited the chemical kinetic models of the pentane isomers originally developed by Healy et al 9 . In their work, they investigated the effect of implementing thermodynamic and reaction rate updates [10][11][12][13][14][15] , as well as the addition of alternative OOQOOH isomerization pathways, on the combustion properties of pentane isomers. Finally, n-hexane sub-mechanism in Curran et al's 8 heptane model was updated by Zhang et al 6 .…”
Section: Introductionmentioning
confidence: 99%
“…A series of quantum chemical calculations have been reported on the low-temperature oxidation reactions of alkanes [46][47][48][49][50]. However, few of these calculations have been performed for n-hexane or larger fuels.…”
Section: Low Temperature Mechanismmentioning
confidence: 99%
“…Villano et al [49] developed the reaction rate rules for the formation of cyclic ethers and the betascission reactions of H radicals as linear functions of the heat of reaction. Villano et al also reported that the uncertainty in the A-factors is a factor of two, while the uncertainty in the activation energy is ±1 kcal mol -1 .…”
Section: Low Temperature Mechanismmentioning
confidence: 99%
“…This approach was successfully applied by Sumathi et al [11,12], Allen et al [13], Sabbe et al [14][15][16][17], and Wang et al [18,19]. Another approach, where rate rules are derived from a systematic investigation of sets of reactions within a given reaction class using electronic structure calculations performed at the CBS-QB3 level of theory, was reported by Villano et al [20,21]. The survey of the different rate estimation rules, together with their applications, was recently reported by Carstensen and Dean [22].…”
Section: Introductionmentioning
confidence: 99%